Crystal structure of pemetrexed disodium heptahydrate, C20H33N5Na2O13 (Alimta). Issue 2 (27th February 2018) - Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of pemetrexed disodium heptahydrate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Pemetrexed disodium heptahydrate crystallizes in space group P2 1 (#4) with a = 11.732 697(27), b = 5.244 195(14), c = 21.689 00(6) Å, β = 92.663 90(20) °, V = 1333.051(6) Å 3, and Z = 2. Each of the two ionized carboxylate groups acts as a unidentate ligand to a Na cation. The remaining five positions of the octahedral coordination spheres are occupied by water molecules. The Na octahedra share an edge to form pairs. These pairs share corners to form chains along the b -axis. All of the water molecule hydrogen atoms act as hydrogen bond donors. In addition the hydrogen atoms associated with the nitrogen atoms and amino groups of the pemetrexed anion were also observed to act as hydrogen bond donors. The powder pattern has been submitted to the International Centre for Diffraction Data (ICDD) for inclusion in the Powder Diffraction File ™ .